2022
DOI: 10.1002/vms3.842
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural and synovial lipomatosis in a 3‐year‐old Eurasian dog receiving sustained steroid therapy

Abstract: This report describes a spinal cord epidural and synovial lipomatosis in a 3‐year‐old neutered male Eurasian dog. This dog presented for ambulatory paraparesis and was previously treated with immunosuppressive dosages of prednisolone for 2 years. Computed tomography (CT) myelography and magnetic resonnance imaging (MRI) images identified dorsal compression of the thoraco‐lumbar spinal cord by hypertrophic epidural fat. Histological examination identified extensive well‐differentiated mature adipose tissue in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Considering the previous case reports and the present case, many characteristics of SEL in dogs seem to be similar to those of human SEL. In a previous case report, cauda equina syndrome occurred because of the accumulation of epidural fat compressing the cauda equina in the lumbosacral spinal canal (11), and ambulatory paraparesis occurred by hypertrophic epidural fat in T8 to L3 vertebral canal segment (16). In this case, the patient's clinical symptoms were caused by hypertrophy of the epidural adipocytes pressing the spinal cord from dorsal to ventral and may be exaggerated by con- current IVDD pressing the spinal cord from ventral to dorsal.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Considering the previous case reports and the present case, many characteristics of SEL in dogs seem to be similar to those of human SEL. In a previous case report, cauda equina syndrome occurred because of the accumulation of epidural fat compressing the cauda equina in the lumbosacral spinal canal (11), and ambulatory paraparesis occurred by hypertrophic epidural fat in T8 to L3 vertebral canal segment (16). In this case, the patient's clinical symptoms were caused by hypertrophy of the epidural adipocytes pressing the spinal cord from dorsal to ventral and may be exaggerated by con- current IVDD pressing the spinal cord from ventral to dorsal.…”
Section: Discussionmentioning
confidence: 71%
“…Since then, many studies have reported the clinical characteristics, prevalence, pathophysiology, and treatment of SEL (7,19,21). In veterinary medicine, there have been no related reports except for the studies on idiopathic SEL in a dachshund dog (11) and steroid-induced SEL in a Eurasian dog (16). Thus, little is known regarding this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,15 This entity has been included in some studies of the concept of lipomatosis, understood as a benign process characterized by the overgrowth of unencapsulated adipose tissue in various locations. 11,16,17 In dogs, lipomatosis has been described in the parotid salivary glands, 18 pancreas, 19 and simultaneously in the tarsal joint and epidural space. 11 Therefore, in cases of clinical suspicion, it may be appropriate to evaluate other potential lesions in animals at the time of diagnosis, given the possibility of systemic or multiple-site involvement.…”
Section: Discussionmentioning
confidence: 99%